Industrial byproducts acidification to produce microbial substrates - Sousa, Rita Daniela Marques (2016)
The excessively use of fossil fuels led to the necessity of more sustainable processes using renewable resources, such as biomass. Due to its abundance, low cost and broad availability, lignocellulosic biomass is a promising substrate for the production of chemicals and energy, among others. Short-chain organic acids (SCOA) have a great potential not only due to their wide applicability, but also to the fact that they can be produced biologically through acidogenic fermentation (AF) from renewable resources, such hardwood sulfite spent liquor (HSSL). The optimization and control of this process is crucial and comprises the monitoring of parameters such as temperature, pH, organic loading rate, sludge and hydraulic retention times, origin of the inoculum and reactor type. In the present study, the AF of HSSL was evaluated in a continuous stirred tank reactor (CSTR), without (CSTR1) and with pH control (CSTR2). For CSTR1, two retention times were tested, 2.34 and 3.01 days, being the average SCOA concentrations of 3.10 and 3.53 gCOD/L achieved. For CSTR2, three pH values were tested, pH 6, 7 and 8. The average SCOA concentrations achieved were 2.36, 2.38 and 2.27 gCOD/L, respectively. Lastly, a moving bed biofilm reactor (MBBR) was also tested and an average concentration of 2.71 gCOD/L of SCOA was obtained. Generally, the main SCOA produced were acetic, propionic and butyric acids. The batch experiments performed, plus the results from all the reactors, allowed to conclude that pH present a decisive influence on the SCOA profiles achieved.